Powiązania między stopami procentowymi w Polsce, USA i strefie euro - Rembeza, Jerzy; Przekota, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper examines linkages among interest rates in Poland, the USA and in the euro area. Integration and cointegration framework was used. The data used are daily, weekly and monthly interest rates from 02.01.2001 to 24.05.2007. It was found long-term relationship among Polish and foreign markets. The results of short-run analysis show that Polish interest rates are more closely linked to that of euro area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 514-523